Seams on a Mannequin : A catalogue to integrate tailors and designers into the urban fabric of Rosebank. - Hlongwane, Siphathisiwe (My University, 2013)
Perceptions determine the way in which we view people and in turn how we are viewed. Just as clothing can disguise the true identity of a person, facades can mask the real character of a building (Craik, 1994). These layers affect a lot of our choices: which building we will enter, where we will choose to shop, what we will purchase, and how much we are willing to spend on the product (Solomon, 1999). A large number of garment makers are not as successful as they could be, as a result of negative perceptions. Despite that Johannesburg is in a post apartheid era many people are still marginalized and located in less affluent parts of the city. Seams on a mannequin is an exploration into how architecture can break down perceptions about social standing and values which have lead to the marginalization of highly skilled garment makers. These garment makers have been placed in buildings of less value, they end up generating less income than the high end brands and yet they are able to provide such a specialized service. The Mannequin is a building designed with the intention of illustrating that garment makers can be able to sustain themselves if they are located in an upmarket precinct in which there is the desired client base for the garment makers. The building will be located in Rosebank, a suburb in which there will be an opportunity for the garment makers to be exposed to the relevant clientele and also where upcoming designers would want to be located. Architecture may be used to brand the spaces from which these garment makers operate, thereby creating positive perceptions about them and the value of their products. This thesis proposes to add another layer to the existing urban fabric of Rosebank. A layer which will facilitate the efficient production, and the appreciation of the value, of customized clothing in the local context. The building will act as a seam- stitching together this new layer with the existing urban fabric. The building is titled the mannequin because it may be dressed up and dressed down. This creates opportunities for it to take different characters, through its unique ability to change through seasons, time of day and trends. The hope is that the perceptions, which people have about the value of the service provided by tailors, will be deconstructed. This should initiate a higher awareness of the value in customized, and not just branded, garments and thereby produce a higher income for the tailors, and designers, so that they may be able to self sustain in upmarket precincts.